Factors influencing innovation performance of China’s high-end manufacturing clusters: Dual-perspective from the digital economy and the innovation networks - Zhang, Liping; Xiong, Kaiqi; Gao, Xinzhi; Yang, Yi (Frontiers in Psychology, 2022)
In the era of digital economy, the role of innovation resources in high-quality economic growth has become increasingly prominent. There are quite a few studies on influencing factors of innovation performance. However, innovation performance is rarely linked to the digital economy and innovation networks. The purpose of this study is to explore the factors that affect the innovation performance of high-end manufacturing clusters in China based on the dual perspectives of digital economy and innovation network. A total of 194 valid questionnaires were collected. And structural equation modeling has been used to test the proposed research models and hypotheses.The results indicated that, the higher the centrality of the innovation network, the more the cluster enterprises can play the centrality advantage, which has a significant positive impact on the innovation performance of the cluster. Similarly, both the strength and density of innovation networks also impacted on cluster innovation performance, but to a lesser extent. We also found that the digital empowerment derived from the digital economy can help build the existing cluster network, strengthen the connection between clusters, which further strengthen the effect of the cluster innovation network on innovation performance. Implications for digital economy and innovation networks to improve the quality of innovation performance are provided.